In situ process monitoring in selective laser sintering using optical coherence tomography - Gardner, Michael R. (Opt Eng, 2018)
Selective laser sintering (SLS) is an efficient process in additive manufacturing that enables rapid part production from computer-based designs. However, SLS is limited by its notable lack of in-situ process monitoring when compared to other manufacturing processes. We report the incorporation of optical coherence tomography into an SLS system in detail and demonstrate access to surface and sub-surface features. Video frame rate cross-sectional imaging reveals areas of sintering uniformity and areas of excessive heat error with high temporal resolution. We propose a set of image processing techniques for SLS process monitoring with OCT and report the limitations and obstacles for further OCT integration with SLS systems.